Thermal comfort assessment of a surgical room through computational fluid dynamics using local PMV index. - Rodrigues, Nelson J. O.; Oliveira, Ricardo F.; Teixeira, Senhorinha F. C. F.; Miguel, Alberto Sérgio; Teixeira, José Carlos; Baptista, João S. (Work, 2015)
BACKGROUND: Studies concerning indoor thermal conditions are very important in defining the satisfactory comfort range in health care facilities. OBJECTIVE: This study focuses on the evaluation of the thermal comfort sensation felt by surgeons and nurses, in an orthopaedic surgical room of a Portuguese hospital. METHODS: Two cases are assessed, with and without the presence of a person. Computational fluid dynamic (CFD) tools were applied for evaluating the predicted mean vote (PMV) index locally. RESULTS: Using average ventilation values to calculate the PMV index does not provide a correct and enough descriptive evaluation of the surgical room thermal environment. As studied for both cases, surgeons feel the environment slightly hotter than nurses. The nurses feel a slightly cold sensation under the air supply diffuser and their neutral comfort zone is located in the air stagnation zones close to the walls, while the surgeons feel the opposite. It was observed that the presence of a person in the room leads to an increase of the PMV index for surgeons and nurses. That goes in line with the empirical knowledge that more persons in a room lead to an increased heat sensation. CONCLUSIONS: The clothing used by both classes, as well as the ventilation conditions, should be revised accordingly to the amount of persons in the room and the type of activity performed.